PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN GOOD CORPORATE GOVERNANCE PADA KUALITAS LABA - Wati, Gahani Purnama; Putra, I Wayan (E-Jurnal Akuntansi, 2017)
Quality of earnings is earnings that reflects the continuation of earnings in the future, which is determined by the components of accrual and cash condition that indicates the actual financial performance.  In This study aims to determine to the effect of the firm size, capital structure and good corporate governance to the quality of earnings. This research was conducted at the Indonesian Stock Exchange by selecting a sample of companies listed in the CGPI in 2010 to 2014. Samples were obtained by 60 by purposive sanpling method. The analysis technique used in this research is multiple linear regression. The results of this study indicate that the good corporate governance positive effect on quality of earnings due to the good corporate governance that capable to increase the firm performance so that effect to increase the quality of earnings.
Keywords: Firm Size, Capital Structure, Good Corporate Governance, Quality of Earnings